Comparative transcriptomic and proteomic analyses of two salt-tolerant alfalfa (Medicago sativa L.) genotypes: investigation of the mechanisms underlying tolerance to salt - Hang, Jiahui; Song, Ting; Zhang, Ling; Hou, Wenjun; Liu, Xiaoxia; Ma, Dongmei (Frontiers in Plant Science, 2024)
Abiotic stressors such as salt stress restrict plant development and output, which lowers agricultural profitability. In this study, alfalfa (Medicago sativa L.) varieties with different levels of salt tolerance were examined using high-throughput RNA sequencing (RNA-Seq) and Tandem Mass Tags (TMT) technologies to study the reactions of the root systems to salt stress, from transcriptomics and proteomics perspectives. To explore the molecular mechanisms of alfalfa under salt stress conditions, the transcriptomes and proteomics of two comparative alfalfa genotypes, Atlantic (AT) and ZhongMu-1 (ZM-1), were evaluated after 2 h and 6 h of treatment with 150 mM NaCl. The results showed that under salt stress for 2 h, 1810 differentially expressed genes (DEGs) and 160 differentially expressed proteins (DEPs) in AT were screened, while 9341 DEGs and 193 DEPs were screened in ZM-1. Under salt stress for 6 h, 7536 DEGs and 118 DEPs were screened in AT, while 11,754 DEGs and 190 DEPs were screened in ZM-1. Functional annotation and pathway enrichment analyses indicated that the DEGS and DEPs were mainly involved in the glutathione metabolism, biosynthesis of secondary metabolites, glycolysis/gluconeogenesis, carbon fixation in photosynthetic organisms, and photosynthesis pathways. A series of genes related to salt tolerance were also identified, including GSTL3 and GSTU3 of the GST gene family, PER5 and PER10, of the PER gene family, and proteins such as APS and COMT, which are involved in biosynthesis of secondary metabolites. The results of this study provide insights into salt resistance mechanisms in plants, and the related genes and metabolic pathways identified may be helpful for alfalfa breeding in the future.Alfalfa (Medicago sativa L.) is a perennial herbaceous legume and one of the world's most significant feed crops. Alfalfa exhibits remarkable tolerance to cold temperatures, salinity, and drought.